Research of Microbial-gel Combined Flooding Technology of Ba19 Block in Baolige Oilfield. Issue 1 (June 2021) - Qiu, Liangliang
Abstract: Bal9 fault block is a medium-high temperature (58°C) reservoir in Baolige Oilfield. The crude oil is characterized by poor physical properties which has high wax and high gum content. The oil-water viscosity ratio is high and this leads to a low water flooding efficiency. The reservoir heterogeneity is high and the contradictions between layers are prominent. According to the characteristics of the oilfield, a microbial-gel combined flooding technology with the microbial flooding as the main body and the gel flooding as the auxiliary is developed to improve the overall development effect of the oilfield water flooding. Microorganism can improve the physical properties of crude oil, and appropriate gel flooding should be carried out to enlarge the sweep volume of microorganism work and improve the effect of microbial-gel combined flooding. By continuous application of this technology in Baolige Oilfield, the concentration of microorganisms is maintained at about 10 6 a/ml, and the whole microbial field is formed. The average annual reduction rate of crude oil is 48.1%. The microbial-gel combined flooding technology is verified to increase the recovery factor by 9.5%. Since the combined flooding was carried out in 2010, the recoverable reserves of the Ba19 block increased by 630, 600 tons.